Impact of obesity on short‐term outcomes of laparoscopic colorectal surgery for Japanese patients with colorectal cancer: A multicenter study. Issue 3 (27th October 2020) - Yamashita, Mariko; Tominaga, Tetsuro; Nonaka, Takashi; Fukda, Akiko; Moriyama, Masaaki; Oyama, Syosaburo; Tanaka, Kenji; Hamada, Kiyoaki; Araki, Masato; Sumida, Yorihisa; Takeshita, Hiroaki; Hisanaga, Makoto; et al.
Abstract: Introduction: The impact of obesity on short‐term outcomes after laparoscopic colorectal surgery (LAC) in Asian patients is unclear. The purpose of the present multicenter study was to evaluate the safety and feasibility of LAC in obese Japanese patients. Methods: We retrospectively reviewed 1705 patients who underwent LAC between April 2016 and February 2019. Patients were classified according to body mass index (BMI): non‐obese (BMI < 25 kg/m 2, n = 1335), obese I (BMI 25‐29.9 kg/m 2, n = 313), and obese II (BMI ≥30 kg/m 2, n = 57). Clinical characteristics and surgical outcomes were compared among the three groups. Results: The proportion of patients with comorbidities (non‐obese, 58.1%; obese I, 69.6%; obese II, 75.4%; P < .001) and median operation time (non‐obese, 224 minutes; obese I, 235 minutes; obese II, 258 minutes; P = .004) increased significantly as BMI increased. The conversion rate was similar among the groups ( P = .715). Infectious complications were significantly high in obese II patients (non‐obese, 10.4%; obese I, 8.3%; obese II, 28.1%; P < .001). Multivariate analysis revealed that in obese II patients, BMI was an independent predictive factor of infectious postoperative complications (odds ratio 2.648; 95% confidence interval, 1.421‐4.934; P = .002). Conclusion: LAC has an increased risk of postoperative infectious complications in obese II patients, despite improvements in surgical technique. Management of obese II colorectal cancer patients requires meticulous perioperative management.